Haiti after the earthquake [compact disc, unabridged] - Farmer, Paul, 1959- (Highbridge Co., 2011)
On January 12, 2010 a massive earthquake laid waste to Port-au-Prince, Haiti, killing hundreds of thousands of people. Within three days, Dr. Paul Farmer arrived in the Haitian capital, along with a team of volunteers, to lend his services to the injured. In this vivid narrative, Farmer describes the incredible suffering--and resilience--that he encountered in Haiti. Having worked in the country for nearly thirty years, he skillfully explores the social issues that made Haiti so vulnerable to the earthquake--the very issues that make it an "unnatural disaster." Complementing his account are stories from other doctors, volunteers, and earthquake survivors. Haiti after the earthquake will both inform and inspire readers to stand with the Haitian people against the profound economic and social injustices that formed the fault line for this disaster.